Orbital character and electron correlation effects on two- and three-dimensional Fermi surfaces in KFe2As2 revealed by angle-resolved photoemission spectroscopy - Teppei eYoshida (Frontiers in Physics, 2014)
We have investigated orbital character and electron correlation effects on Fermi surfaces in the hole-overdoped iron pnictide superconductor KFe2As2, which shows a low Tc of ~4 K, by angle-resolved photoemission spectroscopy. From the polarization-dependence of the ARPES spectra, we have determined the orbital character of each Fermi surface. Electron mass renormalization of each band is quantitatively consistent with de Haas-van Alphen results. The outer beta and middle zeta Fermi surfaces show large renormalization factor of m*/mb ~6-7, while the inner Fermi surface has a smaller factor m*/mb ~2. Middle hole Fermi surface zeta has strong three-dimensionality compared to other Fermi surfaces, indicating the d3z2-r2 orbital character, which may be related to the octet-line nodes recently observed by laser ARPES. The observed orbital-dependent mass renormalization would give constraints on the pairing mechanism with line nodes of this system.